Clinimetric Evaluation of the Vascular Quality of Life Questionnaire in Patients with Lower Limb Ischaemia. (March 2017) - Conijn, A.P.; Santema, T.B.K.; Bipat, S.; Koelemay, M.J.W.; de Haan, R.J.
Abstract : Objectives: Although commonly used to measure health related quality of life in patients with lower limb ischaemia, the measurement properties of the VascuQol and its assumed underlying health dimensions have not been studied in depth. The objective of this study was therefore to evaluate aspects of reliability and validity of the Dutch version of the VascuQol in patients with intermittent claudication (IC) and critical limb ischaemia (CLI). Methods: Two datasets containing 195 patients with IC and 150 patients with CLI were used. Face validity of the VascuQol was examined in interviews with patients and a survey among health professionals. Homogeneity and structural validity of the VascuQol were assessed using Cronbach's α coefficients and explanatory factor analysis. Furthermore, convergent validity and known group validity were assessed. Results: During the face validity interviews, three items were indicated as less relevant. Homogeneity analysis showed that the α coefficient of the VascuQol was .93, while the symptoms and social domains had α coefficients below the threshold of .70. The original five domains of the VascuQol could not be reproduced. Instead, factor analysis yielded a three factor solution. Moderate correlations were found for the activities, social and emotional VascuQol domains and matching health domains of other patient reported outcome measures (PROMs). Lower convergent correlations were observed for the pain domain and the sumscore of the VascuQol. The VascuQol was able to distinguish between patients' level of HRQL in relation to their disease severity (IC versus CLI patients). Conclusions: There is room for improvement of the VascuQol questionnaire. Further clinimetric studies should be performed to strengthen clinically relevant findings based on this instrument.